Dermatological side effects of cancer treatment: psychosocial implications—a systematic review of the literature - Almeida, Vera (2023)
Cancer is a leading cause of mortality and morbidity all over the world and the second major cause of death in Portugal. Dermatological side effects resulting from cancer treatment have a psychosocial impact on patients’ lives, such as quality of life (QoL), body image, cognitive fusion and social inhibition. This systematic review aimed to explore and synthesize the psychosocial impact of dermatological side effects of cancer treatment, answering the following research objectives: (i) Do the dermatological side effects of the cancer treatment present any psychosocial impact for the patients? (ii) How does the psychosocial impact of the dermatological toxicities of the cancer treatment manifest in patients’ lives? Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed and guided a systematic search through the PubMed, Cochrane Library and PyscNet databases. The considered studies correlate dermatological side effects of cancer treatments and their psychological/psychosocial outcomes. The studies found were all published in peer-reviewed journals. The results obtained established that cancer treatment causes the most varied skin changes, consequently reducing self-esteem and QoL; disturbing body image; and contributing to cases of stress, depression and anxiety. There is still limited literature that profoundly investigates the experience of living with these skin toxicities. The development of research lines to improve knowledge in this field will allow for significant improvements in healthcare for patients undergoing cancer treatment who need to focus more on the psychosocial implications of skin toxicities. The novelty of this review lies in adding knowledge summarizing the psychosocial implications of dermatological side effects of cancer treatment to support healthcare providers in the development of integrative therapeutic strategies for these patients in their clinical practice.